Gebruik van Euphorbia Tirucalli als rubberleverancier en energiegewas - Van Damme, Patrick (Afrika Focus, 1990)
Euphorbia tirucalli has been used as a source for natural rubber at different times in history, especially in southern Africa. The latex resin content is too high to guarantee a good quality product and economic production has never taken off as some had hoped. The fact that the plant is very well adapted to arid and semi arid conditions and can be grown on marginal waste lands makes it a potential energy crop which can be turned into biogas without too much investment in costly technology. The first results obtained in the laboratory and in field conditions (Senegal) are very promising. The latex contains a number of interesting triterpenes which have a very high energy content and could be used in fuel production. Most of these applications have been tested or used in Africa and can offer long-term solutions for old problems, particularly in the case of renewable energy through biomass fermentation. KEY WORDS: rubber, biomass, biogas, triterpenes, energy crop